An assessment of the outcomes of prevention of mother-to-child transmission of HIV services in Addis Ababa, Ethiopia - Tefera G. Negash; Valerie J. Ehlers (AOSIS, 2016)
Background: This article assessed maternal and neonatal outcomes amongst users of prevention of mother-to-child transmission (PMTCT) of HIV services in Addis Ababa, Ethiopia. Objectives: The study aimed to assess the health outcomes (antiretroviral prophylaxis versus antiretroviral treatment, CD4 counts, World Health Organization (WHO) stages of illness, other illnesses) of women who had used these services, as well as the HIV status of their babies and the infant feeding method adopted. Methods: A quantitative, cross sectional, retrospective cohort design was used. Document reviews were conducted with a sample of 384 mother-infant pairs (out of a population of 796) who had used PMTCT services. Results: All respondents were using prophylactic antiretrovirals or antiretroviral therapy, but some were on the wrong treatment based on their CD4 counts. The CD4 counts increased four times more for women on antiretroviral treatment than for those on prophylactic antiretrovirals. The WHO's stages of HIV illness did not improve but deteriorated in some cases, and 52 other illnesses were recorded. Out of the 384 infants, 6.0% (n = 23) were HIV-positive. Most respondents opted for exclusive breast feeding but some used mixed feeding during the first six months of their infants' lives, despite having received health education related to infant feeding options. Conclusion: The respondents' improved CD4 counts were inadequate to improve their World Health Organization stages of HIV illness. Some babies received mixed feeding during the first six months of their lives and 6% of the babies were HIV-positive despite their mothers' utilisation of PMTCT services. Keywords: anti-retroviral therapy (ART), CD4 counts, human immune deficiency virus (HIV), infant feeding counseling and practices, prevention of mother-to-child transmission  of HIV (PMTCT)